UPAYA MENINGKATKAN KEAKTIFAN PESERTA DIDIK KELAS XI IPS 3 MATA PELAJARAN PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN MELALUI METODE KOLABORATIF PADA MASA PEMBELAJARAN JARAK JAUH DI SMA NEGERI 1 WEDI KLATEN - Triningsih Sunarmi (LPPM Universitas Widya Dharma, 2023)
During the Covid-19 pandemic, the education sector underwent a change from face-to-face learning (offline) to an online learning process or distance learning (PJJ). Each lesson, the teaching and learning process is carried out remotely (online) which utilizes the internet network and information and communication technology. The study aims to determine the activity of students in participating in online physical education sports and health learning activities during the pandemic in class XI IPS 3 students at SMA Negeri 1 Wedi. This study uses a collaborative method where this method emphasizes the role of parents during distance learning. Parents play a role in accompanying and motivating children during the learning process. This study used data collection using interview techniques, observations and online literature searches. Then the collected data were analyzed qualitatively descriptively. The results of this study indicate that distance learning in the subject of Physical Education, Sports and Health in class XI IPS 3 SMA Negeri 1 Wedi, students, have increased their activeness in participating in the distance learning process. The number of students who collected assignments before the application of the collaborative method was 60%, after applying the collaborative method, the number of students who collected assignments was 90%.